A Genome-Wide Association Study of Coleoptile Length in Different Chinese Wheat Landraces - Ma, Jun; Lin, Yu; Tang, Si; Duan, Shuonan; Wang, Qing; Wu, Fangkun; Li, Caixia; Jiang, Xiaojun; Zhou, Kunyu; Liu, Yaxi (Frontiers in Plant Science, 2020)
From the perspective of wheat yield improvement, the coleoptile is vital for successful crop establishment, and long coleoptile lengths (CLs) are preferred in wheat-growing regions where deep planting is practiced. To determine the genetic basis of CL, we performed a genome-wide association study on a set of 707 Chinese wheat landraces using 18594 single-nucleotide polymorphisms and 38678 diversity array technology sequencing markers. We accordingly detected a total of 29 significant markers (−log10 (P) > 4.76) distributed on chromosomes 2B, 2D, 3A, 4A, 5A, 6A, 6B, 6D, and 7B. Based on linkage disequilibrium decay distance, we identified a total of 17 quantitative trait loci associated with CL, among which QCl.sicau-6B.2, located at 508.17–509.26 Mb on chromosome 6B, was recognized as a novel major locus. We subsequently developed a high-resolution melt marker for QCl.sicau-6B.2, which was validated in an F2:3 population. Our findings provide important insights into the genetic mechanisms underlying coleoptile growth and could be applied to marker-assisted wheat selection.